PENGARUH E-COMMERCE TERHADAP FLUKTUASI HARGA DAN PENINGKATAN PENDAPATAN PETANI CABAI RAWIT - Padapi, Astrini; Mursalat, Aksal; Haryono, Iranita; Fitriyah, Nurul (Jurnal AGRISEP, 2021)
This paper is aimed to examine how the influence of e-commerce use on the income of cayenne pepper farmers, but it is related to the price fluctuation of cayenne pepper. The price fluctuation of raw chilli here acts as an intermediate variable so that this research will be analyzed using Path Analysis. This research uses a quantitative design with a case study research technique. This research was conducted in Ongkoe Village, to be precise in the Machero neighborhood, Belawa District, Wajo Regency, South Sulawesi. The results of path analysis illustrate that indirectly the use of e-commerce through fluctuations in chili prices has a significant effect on increasing farmers' income. Even though it is of small value, it is hoped that farmers can find and take advantage of existing e-commerce in carrying out their daily activities. It is hoped that farmers can find and utilize e-commerce in order to bypass long marketing channels so that consumers do not get higher prices and farmers can sell their crops at a satisfactory price.